Pengembangan Dan Pemberdayaan Masyarakat Melalui Sasirangan: Kolaborasi Antar Mahasiswa/i UIN Antasari Banjarmasin, IPB University, dan STIPER Amuntai di Desa Hukai, Kecamatan Juai, Kabupaten Balangan, Kalimantan Selatan - Alfulaila Noor; Aulia ‘Azizah; Hilya Tuttoyyiba; Junaidi; Laila Salsabila; Muhammad Saman; Rosiana (Fakultas Tarbiah Institut Agama Islam (IAI) Hamzanwadi Pancor, 2023)
Sasirangan fabric is a typical icon of South Kalimantan which is widely known for it’s motifs and uniqueness. Community development and empowerment through Sasirangan is to improve community welfare and empowerment through the use of traditional Sasirangan art. Hukai Village is also one of the places where we can find skilled Sasirangan craftsmen and learn about their dyeing techniques. The method that we used in this project is descriptive qualitative and the data includes the technique and process of dyeing Sasirangan fabric. Data was taken through observation and interviews. This collaboration adds insight and knowledge to participants, especially on how to dye Sasirangan fabric. This collaboration also helps in marketing the Sasirangan fabric models in Hukai Village to the outside community. This also shows the potential of Sasirangan as a means of promoting local culture, developing skills and empowering communities.